Selling Point Influincer di Sosial Media : Studi Kasus Analisis Resepsi Influencer Keanu Angelo Pada Mahasiswa FISIP UHAMKA - Vilya Dwi Agustini; Novi Andayani Praptiningsih (Prisani Cendekia Institute, 2022)
In the past decade the shift of old media to new media has caused various phenomena. Among other things, the appearance of an influincer of celebrity. Personal branding ability is a necessity to captivate the herarts of the audience. Some harsh words, a differebt appearance from most men often shows the nightlife to be a “selling point” of a @Keanuagl. Stuart Hall, as a reviewer of media tekxts in the encoding and decoding process, sees media audiences as active organs. There are different understandings and interpretations, Hall divides the media audience into three positions ammong othersL dominant-hegemonic reading, negotiated reading and opposiotional-hegemonic reading